Pengembangan E-Modul Menggunakan Canva Pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Agustina, Dea; Arwin, Arwin (Universitas Negeri Padang, 2024)
This research was motivated by a problem, namely the minimal use of technology-based teaching materials in schools. The reason is due to the teacher's lack of ability to design teaching materials for science and science learning in class IV. This research uses Research and Development (R&D) research. The development model used is ADDIE, namely Analysis, Design, Develop, Implement, Evaluate. Research data is obtained from validity (material, language and media). Practicality data from student and teacher response questionnaires. The effectiveness test is carried out by giving test questions to students. This research obtained teaching materials that were valid, practical and effective to use. The final validity result obtained 92.33% and was declared